SCIENTIFIC LEADERS FOR THE FUTURE: PRIMARY AND SECONDARY EDUCATION - Nascimento,Fernanda Amorim de Morais (2015)
Objective: To present a high school insertion pilot project in post graduate programs (PPG) and discuss the mechanisms for the formation of leaders in science. Methods: This study presents a review and pilot project. Bibliographic search occurred in sites of CAPES, MEC, SciELO and library of virtual books from January/ 2014 to February/2015. The pilot is in PPG-Medicine III Translational Surgery/UNIFESP and Pathophysiology and Surgical Sciences / UERJ. The junior undergraduate students (ICj) came from public school and develop scientific activities: scientific meetings, graduation and inclusion in research projects. The evaluation will occur at the end of one year, with the results essays, reports and participation in scientific events. Results: In Brazil, one of the main challenges of education is the high average years of study. The PNPG (2011-2020) shows the insertion of basic education in all PPG. In the Pathophysiology and Surgical Sciences/UERJ there are currently 11 high school students who have followed the scientific meetings and are being prepared for the inclusion in research projects. There was 30% of absence, owing to the high school hours. This result and the experience allow creating future alternatives to enhance the integration project. Conclusion: The leadership in science is formed from a complex relationship between basic education and investment in research. PPG-Medicine III courses follow the vanguard with initiatives focused on scientific and technological development. Thus, projects involving basic education students represent promoter model and environment leaders.